Autonomous and smart cleaning mobile robot system to improve the maintenance efficiency of solar photovoltaic array - Megantoro, Prisma; Abror, Abdul; Syahbani, Muhammad Akbar; Anugrah, Antik Widi; Perkasa, Sigit Dani; Setiadi, Herlambang; Awalin, Lilik Jamilatul; Vigneshwaran, Pandi (Institute of Advanced Engineering and Science, 2023)
A solar photovoltaic (PV) array is part of a PV power plant as a generation unit. PV array that are usually placed on top of buildings or the ground will be very susceptible to dirt and dust. Thus, this dirt and dust will be able to reduce the performance and work efficiency of the generation unit. Cleaning PV arrays by manpower requires high effort, cost, and risk, especially in higher location. This study presents the design of a mobile robot that is used to replace human labor to clean PV arrays. That way, the PV array maintenance steps can reduce operational costs and risks. This intelligent controlled mobile robot can maneuver safely and efficiently over PV arrays. gyroscope and proximity sensors are used to detect and follow the sweep path over the entire PV array area. Proportional integral derivative (PID) control test makes the robot can stabilize in about 5.72 seconds to keep on the track. The smart PV cleaning robot has average operation time about 13 minutes in autonomous mode and 20-24 minutes in manual mode. The operation of the robot is effective to give more efficiency on the use of energy, time, and maintenance costs of PV array system.